Characterization and phylogenomics of the complete mitochondrial genome of the polyzoic cestode Gangesia oligonchis (Platyhelminthes: Onchoproteocephalidea). (2020) - Li, W.X.; Zhang, D.; Fu, P.P.; Song, R.; Zou, H.; Li, M.; Wu, S.G.; Wang, G.T.
Abstract: The order Onchoproteocephalidea (Eucestoda) was recently erected to accommodate the hook-bearing tetraphyllideans and the proteocephalideans, which are characterized by internal proglottization and a tetra-acetabulate scolex. The recognized subfamilies in the Proteocephalidae appeared to be non-monophyletic based on 28S recombinant DNA (rDNA) sequence data. Other molecular markers with higher phylogenetic resolution, such as large mitochondrial DNA fragments and multiple genes, are obviously needed. Thus the mitochondrial genome of Gangesia oligonchis, belonging to the putative earliest diverging group of the Proteocephalidae, was sequenced. The circular mitogenome of G. oligonchis was 13, 958 bp in size, and contained the standard 36 genes: 22 transfer RNA genes, two rRNA genes and 12 protein-coding genes, as well as two major non-coding regions. A short NCR and a large NCR (lNCR) region were 216 bp and 419 bp in size, respectively. Highly repetitive regions in the lNCR region were detected with that of 11 repeat units. The mitogenome of G. oligonchis shared 71.1% nucleotide identity with Testudotaenia sp. WL-2016. Phylogenetic analyses of the complete mitochondrial genomes with Bayesian inference and maximum likelihood methods indicated that G. oligonchis formed a sister clade with Testudotaenia sp. WL-2016 with maximum support. The ordinal topology is (Caryophyllidea, (Diphyllobothriidea, (Bothriocephalidea, (Onchoproteocephalidea, Cyclophyllidea)))). The mitogenomic gene arrangement of G. oligonchis was identical to that of Testudotaenia sp. WL-2016. Both mitogenomic and nuclear sequence data for many more taxa are required to effectively explore the inter-relationships among the Onchoproteocephalidea.